Studi Perencanaan Ulang Perpipaan Sistem Filtrasi Air Skala Rumah Tangga - Dibyo Setiawan; Jakariya; Rani Anggrainy; Linda Wijayanti; Melisa Mulyadi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
Clean water is a primary necessity for human survival, but due to limited access to clean water sources, wells are often used to meet this need. However, water from wells cannot be used directly because its quality varies depending on the soil conditions. Due to these differences, a filtration system needs to be installed in the treatment of raw water from the well. In the process, well water, after being processed through the filtration system, experiences a decrease in flow rate before being stored in water tanks. This creates a problem, namely excessive electricity consumption and insufficient water flow for household use. In this research, the researcher attempts to implement the SNI (Indonesian National Standard) standards in household-scale clean water treatment, whereas previous research focused more on water quality testing. The objectives of this research are to reduce electricity consumption and increase water flow to meet household needs. Regarding the research method, the researcher conducted a literature review, data collection, pre-improvement testing, redesigned pipeline planning, performance testing of the improvement results, and analysis of the outcomes. The results of this research show that for the 1-liter container testing, the required time has increased, with the fastest time being 6.4 seconds and the slowest being 6.7 seconds, compared to the initial testing, which had a range of 13.2 seconds to 13.6 seconds. As for electricity consumption, there has been a significant decrease, from 2.76 A in the initial testing to 1.76 A, resulting in an average power consumption of 200.3 watt, compared to the previous 603.7 watt.